Upaya Meningkatkan Hasil Belajar IPA Fisika Pada Kompetensi Dasar Mendeskripsikan Muatan Listrik Metode Cognitive Style Mapping ( CSM) Siswa Kelas IXA SMP Negeri 1 Sangalla’ Tana Toraja (Jurnal Keguruan dan Ilmu Pendidikan, 2019)
The aim of this study was to examine student activities in learning through the Cognitive Style Mapping (CSM) Method. This research was carried out in Physics Science in SMP Negeri 1 Sangalla First Semester Academic Year 2016/2017. The Subject of this study were students of class IXA. Data collection methods use the results of the final test of each cycle to determine student learning success, the results of observations and questionnaire results given to students to determine student responses to the application of learning models through methods CSM. Data collection were using a questionnaire, authentic assessment to obtain learning progress material (level of achievement) Physics Science, observation, interview and document study. The result of this study were consist 3 cycle namely cycle 1, cycle 2 and cycle 3. Cycle I shows the average cognitive learning outcomes is 67 and completeness 63.33%, the average affective learning outcomes is 64 and completeness 66.67% and the average psychomotor learning outcomes is 62 and completeness 60%. Cycle II shows the average cognitive learning outcomes is 69 and completeness 83.33%, the average affective learning outcomes is 76 and completeness 89% and the average psychomotor learning outcomes is 74 and 76.67% completeness. Cycle III shows the average cognitive learning outcomes is 82 and completeness 93.33%, the average affective learning outcomes is 84 and 100% completeness and the average psychomotor learning outcomes is 82 and 100% completeness.The conclusion was the application of learning models through the CSM method can improve the learning outcomes of Physics Science in basic competencies describing electric charges to understand the symptoms of static electricity and their relationship to everyday life. The application of learning models through the CSM method in learning Physics science can improve enthusiasm in teaching and learning activities.